Rubber composition
Patent Information
- Application Number
- CN202180103680.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-29
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2041-10-29
AI Technical Summary
[0007]然而,抗臭氧蜡的缺点是会向胎侧外部迁移,露出白斑,从而不利于轮胎的美观
[0022]这种特定的橡胶组合物能够在不使抗臭氧性能变差的情况下出人意料地改进起霜性能。
Smart Images

Figure GDA0005024955150000211 
Figure GDA0005024955150000221 
Figure GDA0005024955150000222
Abstract
Description
Technical Field
[0001] The field of this invention is the field of rubber compositions, particularly rubber compositions for rubber articles in contact with ambient air, more particularly rubber compositions for tires, shoes, conveyor belts or rubber tracks, and even more particularly rubber compositions for tires, especially rubber compositions for tire sidewalls. Background Technology
[0002] Rubber products exposed to ambient air deteriorate due to ozone. A known solution is to add anti-ozone wax to the rubber composition used in rubber products to achieve good ozone resistance.
[0003] List of referenced files
[0004] Patent documents
[0005] PTL 1: JP6881627
[0006] Patent document 1 discloses a rubber composition for tire sidewalls, the rubber composition comprising rubber components, modified rubber powder and anti-ozone wax, and having excellent anti-ozone properties.
[0007] However, a drawback of anti-ozone wax is that it can migrate to the outer sidewall, revealing white spots, which is detrimental to the tire's appearance. This phenomenon is called blooming. Summary of the Invention
[0008] Technical issues
[0009] During the research, the inventors discovered a specific rubber composition specifically designed for use in rubber products, more particularly in tires, shoes, conveyor belts or rubber tracks, and even more particularly in tire sidewalls. This rubber composition can unexpectedly improve blooming properties without compromising ozone resistance.
[0010] The expression "based on" or "composition-based" should be understood to mean that the composition comprises a mixture of various basic components used, in-situ reaction products, or both, some of which are capable, intended, or intended to react with each other at least partially during various stages of the manufacture of the composition, or during the curing or modification of the composition after the initial preparation of the composition. Therefore, compositions used in this invention can be different in a non-crosslinked state and in a crosslinked (vulcanized) state.
[0011] The term "phr" refers to parts by weight per 100 parts of elastomer in the context of preparation prior to curing of the composition. That is, in the presence of rubber powder, the term "phr" refers to parts by weight per 100 parts of "new" elastomer, thus removing the elastomer contained in the rubber powder from the base of 100.
[0012] In this specification, unless otherwise expressly stated, all percentages (%) shown are weight percentages (wt%).
[0013] The term "elastomer matrix" is understood to mean all elastomers present in the rubber composition in a given composition.
[0014] In this specification, unless otherwise expressly stated, each Tg DSC (Glass transition temperature) is determined in a known manner by DSC (differential scanning calorimetry) according to standard ASTM D3418-08.
[0015] Any numerical interval expressed as “between a and b” represents a range of values greater than “a” and less than “b” (i.e., excluding the endpoints a and b), while any numerical interval expressed as “between a and b” means a range of values from a to b (i.e., including the strict endpoints a and b).
[0016] When referring to a "major" compound, this is understood within the meaning of this invention to mean that the compound is dominant among compounds of the same type in the composition, that is, it is the compound that accounts for the largest weight percentage, preferably greater than 50% by weight, and more preferably greater than 75% by weight, among compounds of the same type. Thus, for example, a major polymer is the polymer that accounts for the largest weight percentage of the total polymers in the composition. Similarly, a "major" filler is the filler that accounts for the largest weight percentage of the fillers in the composition. For example, in a system containing only one polymer, that polymer is dominant within the meaning of this invention; in a system containing two polymers, the major polymer accounts for more than half the weight of the polymers. Conversely, a "minor" compound is a compound that does not account for the largest weight percentage among compounds of the same type.
[0017] Within the meaning of this invention, when referring to a “major” unit (or monomer) within the same compound (or polymer), it is understood to mean that the unit (or monomer) is major among the units (or monomers) forming the compound (or polymer), that is, it is the unit (or monomer) that constitutes the largest weight portion among the units (or monomers) forming the compound (or polymer). Thus, for example, a resin mainly composed of units derived from C5 monomers is a resin in which the C5 unit constitutes the largest weight portion of all units constituting the resin. In other words, a “major” monomer or a combination of “major” monomers is the monomer (or combination of monomers) that constitutes the largest weight portion in the polymer. Conversely, a “minor” monomer is a monomer that does not constitute the largest molar portion in the polymer.
[0018] The compounds mentioned in this specification may be of fossil or bio-based origin. In the case of bio-based origin, they may be produced partially or entirely from biomass, or obtained from renewable raw materials derived from biomass. Polymers, plasticizers, fillers, etc., are particularly relevant.
[0019] Solution to the problem
[0020] A first aspect of the present invention is a rubber composition based at least on an elastomer matrix, an anti-ozone wax, and rubber powder, wherein the elastomer matrix comprises an isoprene elastomer; the total amount of the isoprene elastomer is greater than 27.00 wt% / 100.00 wt% of the rubber composition; the total amount of the anti-ozone wax is greater than 0.60 wt% / 100.00 wt% and less than 1.70 wt% / 100.00 wt% of the rubber composition; the rubber powder comprises rubber powder particles with a particle size of less than 74 μm; and the weight ratio of the total amount of rubber powder particles with a particle size of less than 74 μm to the total amount of anti-ozone wax is greater than 0.65.
[0021] Advantages of the present invention
[0022] This particular rubber composition can unexpectedly improve blooming performance without compromising ozone resistance. Detailed Implementation
[0023] Each of the following aspects, embodiments, examples, and variations includes each preferred scope, substance, or both, which may be applied to any other aspect, embodiment, example, and variation of the invention, unless otherwise expressly stated.
[0024] The rubber composition according to the invention is based on an elastomer matrix.
[0025] Generally, the interchangeable terms "elastomer" and "rubber" are used interchangeably in the text.
[0026] "Diene" type elastomers (or broadly "rubber," the two terms being considered synonymous) are understood in a known manner as elastomers that are at least partially (i.e., homopolymers or copolymers) derived from diene monomers (monomers with two conjugated or non-conjugated carbon-carbon double bonds) (meaning one or more).
[0027] These diene elastomers can be divided into two categories: "substantially unsaturated" or "substantially saturated." Generally, "substantially unsaturated" is understood to mean diene elastomers that are at least partially derived from conjugated diene monomers and have a diene source (conjugated diene) unit content greater than 15% (mol%). Therefore, diene elastomers such as butyl rubber or EPDM-type diene / α-olefin copolymers do not fall into the aforementioned definition but can be specifically described as "substantially saturated" diene elastomers (low or very low diene source unit content, always less than 15%). Within the category of "substantially unsaturated" diene elastomers, the term "highly unsaturated" is understood to specifically mean diene elastomers with a diene source (conjugated diene) unit content greater than 50%.
[0028] Although any type of diene elastomer is applicable, substantially unsaturated diene elastomers are preferred.
[0029] In light of these definitions, the term "dien elastomer" as used in the compositions according to the invention is specifically understood to mean:
[0030] (a) Any homopolymer obtained by polymerization of a preferred conjugated diene monomer having 4 to 12 carbon atoms;
[0031] (b) Any copolymer obtained by copolymerization of one or more conjugated dienes with each other or with one or more vinyl aromatic compounds, preferably having 8 to 20 carbon atoms.
[0032] The following are particularly suitable as conjugated dienes: 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-di(C1-C5-alkyl)-1,3-butadiene (e.g., 2,3-dimethyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2-methyl-3-ethyl-1,3-butadiene, or 2-methyl-3-isopropyl-1,3-butadiene), aryl-1,3-butadiene, 1,3-pentadiene, or 2,4-hexadiene. For example, the following are suitable as vinyl aromatic compounds: styrene, (o-, m-, or p-)methylstyrene, commercially available mixtures of "vinyltoluene," p-(tert-butyl)styrene, methoxystyrene, chlorostyrene, vinyltrimethylbenzene, divinylbenzene, or vinylnaphthalene.
[0033] The elastomer matrix in the rubber composition according to the present invention comprises isoprene elastomer.
[0034] Isoprene elastomers are understood to refer to all elastomers that are mainly composed of isoprene monomers.
[0035] According to a preferred embodiment of the present invention, the isoprene elastomer is selected from isoprene polymers, isoprene copolymers, and combinations thereof.
[0036] According to a more preferred embodiment of the above preferred embodiment, the isoprene copolymer is selected from butadiene isoprene copolymer (BIR), styrene isoprene copolymer (SIR), styrene butadiene isoprene copolymer (SBIR), and combinations thereof.
[0037] According to an even more preferred embodiment of the above-mentioned preferred embodiment, the isoprene content of the butadiene isoprene copolymer (BIR) is greater than 50% by weight / 100% by weight and less than 90% by weight / 100% by weight.
[0038] According to a more preferred embodiment described above, the Tg of the butadiene-isoprene copolymer (BIR) is... DSC The temperature ranges from -80℃ to -40℃.
[0039] According to an even more preferred embodiment of the above-mentioned preferred embodiment, the styrene-isoprene copolymer (SIR) has a styrene content greater than 5% by weight / 100% by weight and less than 50% by weight / 100% by weight.
[0040] According to a more preferred embodiment described above, the Tg of the styrene-isoprene copolymer (SIR) is... DSC Temperatures greater than -25℃ and less than -50℃.
[0041] According to an even more preferred embodiment of the above-mentioned preferred embodiment, the isoprene content of the styrene-butadiene-isoprene copolymer (SBIR) is greater than the content of styrene and butadiene.
[0042] According to an even more preferred embodiment of the above-mentioned preferred embodiment, the isoprene content of the styrene-butadiene-isoprene copolymer (SBIR) is greater than 50% by weight / 100% by weight and less than 60% by weight / 100% by weight.
[0043] The total amount of isoprene elastomer in the elastomer matrix of the rubber composition according to the present invention is greater than 27.00% by weight, preferably greater than 27.50% by weight of isoprene elastomer / 100.00% by weight of rubber composition.
[0044] The second aspect of the invention is a rubber composition according to the first aspect, wherein the total amount of isoprene elastomer is greater than 28.00% by weight / 100.00% by weight, preferably greater than 28.50% by weight / 100.00% by weight, and more preferably greater than 29.00% by weight / 100.00% by weight.
[0045] The third aspect of the invention is a rubber composition according to the first or second aspect, wherein the total amount of isoprene elastomer is less than 34.00 wt% / 100 wt%, preferably less than 33.50 wt% / 100 wt%, more preferably less than 33.00 wt% / 100 wt%, even more preferably less than 32.50 wt% / 100 wt%, particularly less than 32.00 wt% / 100 wt%, even more particularly less than 31.50 wt% / 100 wt%, and even more particularly less than 31.00 wt% / 100 wt%.
[0046] A fourth aspect of the invention is a rubber composition according to any one of the first to third aspects, wherein the isoprene elastomer is selected from natural rubber, synthetic polyisoprene, and combinations thereof, and the isoprene elastomer is preferably composed of natural rubber.
[0047] According to the preferred embodiment of the fourth aspect, the synthetic polyisoprene is preferably a synthetic polyisoprene with a cis-1,4 bond content (mol%) greater than 90%, more preferably greater than 95%, and even more preferably greater than 98%.
[0048] The fifth aspect of the invention is a rubber composition according to any one of the first to fourth aspects, wherein the elastomer matrix further comprises a butadiene elastomer.
[0049] The sixth aspect of the invention is a rubber composition according to the fifth aspect, wherein the total amount of butadiene elastomer is less than 31.00 wt% / 100.00 wt%, preferably less than 30.50 wt% / 100.00 wt%, more preferably less than 30.00 wt% / 100.00 wt%, even more preferably less than 29.50 wt% / 100.00 wt%, particularly less than 29.00 wt% / 100.00 wt%, even more particularly less than 28.50 wt% / 100.00 wt%, even more particularly less than 28.00 wt% / 100.00 wt%, advantageously less than 27.50 wt% / 100.00 wt%.
[0050] The seventh aspect of the invention is a rubber composition according to the fifth or sixth aspect, wherein the total amount of butadiene elastomer is greater than 23.00 wt% / 100.00 wt%, preferably greater than 23.50 wt% / 100.00 wt%, more preferably greater than 24.00 wt% / 100.00 wt%, even more preferably greater than 24.50 wt% / 100.00 wt%, particularly greater than 25.00 wt% / 100.00 wt%, and even more particularly greater than 25.50 wt% / 100.00 wt%.
[0051] Butadiene elastomers are understood to refer to all elastomers that are mainly composed of butadiene monomers.
[0052] The eighth aspect of the invention is a rubber composition according to any one of the fifth to seventh aspects, wherein the butadiene elastomer is selected from butadiene polymers, butadiene copolymers and combinations thereof, preferably selected from polybutadiene (BR), styrene-butadiene copolymer (SBR) and combinations thereof.
[0053] According to the preferred embodiment of the eighth aspect, the butadiene elastomer is selected from polybutadiene (BR) and combinations thereof.
[0054] According to a more preferred embodiment of the above preferred embodiment, the content (mol%) of 1,2-units of polybutadiene is greater than 4% and less than 80%.
[0055] According to a more preferred embodiment of the above preferred embodiment, the cis-1,4- content (mol%) of polybutadiene is greater than 80%.
[0056] According to the preferred embodiment of aspect eight, the butadiene copolymer is selected from styrene-butadiene copolymer (SBR), butadiene-isoprene copolymer (BIR), styrene-butadiene-isoprene copolymer (SBIR), and combinations thereof.
[0057] According to a more preferred embodiment of the above preferred embodiment, the butadiene copolymer is selected from styrene-butadiene copolymer (SBR) and combinations thereof.
[0058] According to a more preferred embodiment described above, the glass transition temperature Tg of the styrene-butadiene copolymer (SBR) is... DSC The temperature is greater than -100°C and less than 0°C, preferably greater than -90°C and less than 0°C, more preferably greater than -80°C and less than 0°C, even more preferably greater than -70°C and less than 0°C, and particularly greater than -60°C and less than -10°C.
[0059] According to an even more preferred embodiment of the above-mentioned preferred embodiment, the styrene-butadiene copolymer (SBR) has a styrene content greater than 5 wt% / 100 wt% and less than 60 wt% / 100 wt% of styrene-butadiene copolymer (SBR), and more particularly greater than 20 wt% / 100 wt% of styrene-butadiene copolymer (SBR) and less than 50 wt% / 100 wt% of styrene-butadiene copolymer (SBR).
[0060] According to an even more preferred embodiment of the above-mentioned preferred embodiment, the 1,2-bond content (mol%) of the butadiene portion of the styrene-butadiene copolymer (SBR) is greater than 4% and less than 75%, and the trans-1,4-bond content (mol%) is greater than 10% and less than 80%.
[0061] According to a more preferred embodiment of the above preferred embodiment, the butadiene copolymer is selected from butadiene isoprene copolymer (BIR) and combinations thereof.
[0062] According to an even more preferred embodiment of the above-mentioned preferred embodiment, the isoprene content of the butadiene isoprene copolymer (BIR) is greater than 5% by weight / 100% by weight and less than 50% by weight / 100% by weight.
[0063] According to a more preferred embodiment described above, the Tg of the butadiene-isoprene copolymer (BIR) is... DSC The temperature ranges from -80℃ to -40℃.
[0064] According to a more preferred embodiment of the above-mentioned preferred embodiment, the butadiene copolymer is selected from styrene-butadiene-isoprene copolymer (SBIR) and combinations thereof. The butadiene content of the styrene-butadiene-isoprene copolymer (SBIR) is greater than the content of styrene and isoprene.
[0065] According to a preferred embodiment of the present invention, the elastomer matrix in the rubber composition of the present invention is composed of isoprene elastomer and butadiene elastomer.
[0066] According to another preferred embodiment of the invention, the elastomer matrix in the rubber composition according to the invention comprises another elastomer or other elastomer besides isoprene elastomer and butadiene elastomer.
[0067] Therefore, any elastomer known to those skilled in the art that is not defined as isoprene elastomer or butadiene elastomer as above may be used.
[0068] The rubber composition according to the invention is based on an anti-ozone wax (or an anti-ozone agent wax).
[0069] Anti-ozone waxes are film-forming anti-ozone waxes well known to those skilled in the art. For example, these film-forming anti-ozone waxes can be paraffin wax, microcrystalline wax, or a mixture of paraffin wax and microcrystalline wax. They consist of a mixture of linear and nonlinear alkanes (isoalkanes, cycloalkanes, branched alkanes) derived from the refining of oils or the catalytic hydrogenation of carbon monoxide (Fischer-Tropsch process), primarily comprising chains of at least 20 carbon atoms.
[0070] All anti-ozone waxes known to those skilled in the art can be used, including natural waxes such as candelilla wax or carnauba wax. Furthermore, these waxes can be used in blends.
[0071] Commercially available anti-ozone waxes include Varazon 4959, Varazon 6500 and Varazon 6810 from Sasol, Ozoace 0355 from Nippon Seiro, Negozone 9343 from H&R and H3841 from Yanggu Huatai.
[0072] The rubber composition according to the invention contains an amount of anti-ozone wax greater than 0.60 wt% / 100.00 wt%, preferably greater than 0.65 wt% / 100.00 wt%, and less than 1.70 wt% / 100.00 wt%, preferably less than 1.65 wt% / 100.00 wt%.
[0073] The ninth aspect of the invention is a rubber composition according to any one of the first to eighth aspects, wherein the total amount of anti-ozone wax is greater than 0.70 wt% / 100.00 wt%, preferably greater than 0.75 wt% / 100.00 wt%, more preferably greater than 0.80 wt% / 100.00 wt%, even more preferably greater than 0.85 wt% / 100.00 wt%, particularly greater than 0.90 wt% / 100.00 wt%, and even more particularly greater than 0.95 wt%. The percentage of rubber composition by weight is greater than 1.00% by weight / 100.00% by weight, more particularly greater than 1.05% by weight / 100.00% by weight, more advantageously greater than 1.10% by weight / 100.00% by weight, more advantageously greater than 1.15% by weight / 100.00% by weight, especially greater than 1.20% by weight / 100.00% by weight, and even more particularly greater than 1.25% by weight / 100.00% by weight.
[0074] The tenth aspect of the invention is a rubber composition according to any one of the first to ninth aspects, wherein the total amount of anti-ozone wax is less than 1.60 wt% / 100.00 wt%, preferably less than 1.55 wt% / 100.00 wt%, more preferably less than 1.50 wt% / 100.00 wt%, even more preferably less than 1.45 wt% / 100.00 wt%, particularly less than 1.40 wt% / 100.00 wt%, and even more particularly less than 1.35 wt% / 100.00 wt%.
[0075] According to a preferred embodiment of the invention, the anti-ozone wax contains 50% to 75% by weight of linear alkanes, the linear alkanes containing 30 to 38 carbon atoms, based on the total amount of linear alkanes.
[0076] The rubber composition according to the invention is based on rubber powder (abbreviated as "rubber powder" for the remainder of this document).
[0077] Rubber powder is in granular form and may optionally be made into rubber sheets. Typically, rubber powder is derived from the grinding or micronization of cured rubber compositions that have already been used in their first application (e.g., in tires); they are products of material recycling.
[0078] Rubber powder can be obtained by turning waste tires or other rubber into granules, in which reinforcing materials (such as steel or fibers) and any other contaminants (such as dust, glass, or rock) are removed. "Rubber Chemistry and Technology" discloses numerous methods for grinding vulcanized or cross-linked rubber into rubber powder.
[0079] According to a preferred embodiment of the present invention, the rubber powder is generated from waste tires.
[0080] According to a preferred embodiment of the present invention, the rubber powder is in the form of microparticles.
[0081] The term “microparticle” is intended to refer to particles whose size (i.e., their diameter in the case of spherical particles or their maximum size in the case of unequal-axis particles) is a few micrometers, tens of micrometers, or hundreds of micrometers.
[0082] The rubber powder in the rubber composition according to the present invention comprises rubber powder particles with a particle size of less than 74 μm.
[0083] In the rubber composition according to the present invention, the total weight ratio of the total amount of rubber powder particles with a particle size of less than 74 μm to the total amount of anti-ozone wax is greater than 0.65.
[0084] The eleventh aspect of the present invention is a rubber composition according to any one of the first to tenth aspects, wherein the weight ratio of the total amount of rubber powder particles with a particle size of less than 74 μm to the total amount of anti-ozone wax is greater than 0.70, preferably greater than 0.75, more preferably greater than 0.80, and even more preferably greater than 0.85.
[0085] The twelfth aspect of the invention is a rubber composition according to any one of the first to eleventh aspects, wherein the total amount of rubber powder particles with a particle size of less than 74 μm is greater than 0.90 wt% / 100.00 wt%, preferably greater than 0.95 wt% / 100.00 wt%, more preferably greater than 1.00 wt% / 100.00 wt%, even more preferably greater than 1.05 wt% / 100.00 wt%, particularly greater than 1.10 wt% / 100.00 wt%, and even more particularly greater than 1.15 wt% / 100.00 wt%.
[0086] The total weight of rubber powder particles with a particle size of less than 74 μm in the rubber powder of the rubber composition according to the present invention can be obtained by the particle size distribution determined according to ASTM-D5644-01.
[0087] Alternatively, the particle size distribution of the adhesive powder can be measured using laser particle size analysis on a Malvern mastersizer 3000 device. Measurements can be performed via a liquid approach, after 1 minute of ultrasonic pretreatment followed by ethanol release in alcohol to ensure particle dispersion. Measurements can be performed according to standard ISO-13320-1, and specifically D10 and D50, i.e., the average diameters below which 10% and 50% by weight of the total particle count can be determined, respectively.
[0088] The rubber powder in the rubber composition according to the present invention may include other rubber powder particles with a particle size greater than or equal to 74 μm.
[0089] According to a preferred embodiment of the invention, the rubber powder in the rubber composition is subjected to mechanical treatment, cryogenic treatment, or both mechanical and cryogenic treatment; that is, the rubber powder is ground using a mechanical grinding process, a cryogenic process, or both. In both processes, a magnetic separator is used to remove the steel component, and an air classifier or other separation equipment is used to separate the fiber component. The mechanical grinding process uses various grinding techniques (e.g., crushers, granulators, etc.) to mechanically break down the rubber into small particles. In the cryogenic process, the shredded rubber is frozen at an extremely low temperature and then pulverized into small particles.
[0090] According to a more preferred embodiment of the above preferred embodiment, the rubber powder is subjected to low-temperature treatment according to the micronization process described in US7445170 and US7861958.
[0091] Commercially available rubber powders include, for example, PolyDyne 40, PolyDyne 80, PolyDyne 140, or PolyDyne 200 from Lehigh Technologies.
[0092] According to a preferred embodiment of the present invention, the amount of rubber powder in the rubber composition of the present invention is greater than 1.00 wt% / 100 wt%, preferably greater than 2.00 wt% / 100 wt%, more preferably greater than 3.00 wt% / 100 wt%, and even more preferably greater than 4.00 wt% / 100 wt%.
[0093] According to a preferred embodiment of the invention, the amount of rubber powder in the rubber composition according to the invention is less than 20.00 wt% / 100 wt%, preferably less than 18.00 wt% / 100 wt%, more preferably less than 16.00 wt% / 100 wt%, even more preferably less than 14.00 wt% / 100 wt%, particularly less than 12.00 wt% / 100 wt%, and even more particularly less than 10.00 wt% / 100 wt%.
[0094] The rubber powder in the rubber composition according to the invention may be composed of a composition based on all the components commonly used in rubber compositions for rubber articles.
[0095] According to a preferred embodiment of the invention, the rubber powder in the rubber composition of the invention is composed of an elastomer-based composition.
[0096] According to a more preferred embodiment of the above preferred embodiment, the rubber powder contains an elastomer comprising more than 30% by weight / 100% by weight of the rubber powder, preferably more than 35% by weight / 100% by weight of the rubber powder, more preferably more than 40% by weight / 100% by weight of the rubber powder, the percentage being determined according to ASTM E1131-03.
[0097] According to the preferred embodiment described above or an even more preferred embodiment described above, the elastomer contained in the rubber powder includes a diene elastomer, preferably composed of a diene elastomer.
[0098] According to a further preferred embodiment of the above-mentioned embodiment, the diene elastomer in the rubber powder is selected from polybutadiene, polyisoprene (including natural rubber), butadiene copolymer and isoprene copolymer.
[0099] According to a more preferred embodiment of the above-mentioned embodiment, the molar content of diene source (conjugated diene) units present in the diene elastomer in the rubber powder is greater than 50%, preferably greater than 50% and less than 70%.
[0100] According to a preferred embodiment of the invention, the rubber powder in the rubber composition of the invention is composed of a filler-based composition.
[0101] According to a more preferred embodiment of the above preferred embodiment, the amount of the filler in the rubber powder is greater than 5% by weight and less than 80% by weight, preferably greater than 10% by weight and less than 75% by weight, more preferably greater than 15% by weight and less than 70% by weight of filler / 100% by weight of rubber powder, the percentage being determined according to ASTM E1131-03.
[0102] In this document, the term "filler" is intended to mean any type of filler, whether it is a reinforcing filler (typically nanoparticles with a weight-average size preferably less than 500 nm, particularly greater than 20 nm and less than 200 nm) or a non-reinforcing filler or an inert filler (typically micron-sized particles with a weight-average size preferably greater than 1 μm, for example, greater than 2 μm and less than 200 μm). The weight-average size of the nanoparticles is measured in a manner known to those skilled in the art (for example, according to Section 1.1 of patent application WO 2009 / 083160). The weight-average size of the micron-sized particles can be determined by mechanical sieving.
[0103] According to a more preferred embodiment of the above preferred embodiment, the filler in the rubber powder includes reinforcing filler, which preferably includes reinforcing organic filler, reinforcing inorganic filler, or a combination thereof.
[0104] Any type of reinforcing filler known to be able to reinforce rubber compositions that can be used to manufacture articles may be used, such as reinforcing organic fillers (e.g., at least one type of carbon black) or reinforcing inorganic fillers (e.g., silica (SiO2), alumina (Al2O3), or combinations thereof), which are combined with at least one coupling agent in a known manner.
[0105] According to an even more preferred embodiment described above, the reinforcing filler in the rubber powder includes a reinforcing organic filler, preferably at least one type of carbon black, wherein the reinforcing organic filler preferably comprises more than 50% by weight / 100% by weight, even more preferably more than 60% by weight / 100% by weight, particularly more than 70% by weight / 100% by weight, even more particularly more than 80% by weight / 100% by weight, even more particularly more than 90% by weight / 100% by weight, and advantageously 100% by weight / 100% by weight.
[0106] According to the preferred embodiment described above, the reinforcing filler in the rubber powder includes a reinforcing organic filler, preferably at least one carbon black, wherein the reinforcing organic filler preferably accounts for 20% to 40% by weight of the rubber powder, and even more preferably 25% to 35% by weight of the rubber powder.
[0107] The weight fraction of carbon black can be measured by thermogravimetric analysis (TGA) on a Mettler Toledo model "TGA / DSC1" instrument, according to standard NF T-46-07. Approximately 20 g of sample is introduced into the thermal analyzer, followed by a thermal program of 25°C to 600°C (pyrolytic phase) under an inert atmosphere, and then a thermal program of 400°C to 750°C (oxidizable phase) under an oxidizing atmosphere. The weight of the sample can be continuously measured throughout the thermal program. The organic matter content corresponds to the weight loss relative to the initial weight of the sample measured during the pyrolytic phase. The amount of carbon black corresponds to the weight loss relative to the initial weight of the sample measured during the oxidizable phase.
[0108] All carbon blacks commonly used in tires, especially SAF, ISAF, HAF, FEF, GPF, HMF, SRF, and SRF type carbon blacks (“tire grade” carbon blacks), are suitable as carbon blacks, such as ASTM grade reinforcing carbon blacks of the 100, 200, or 300 series (e.g., N115, N134, N234, N326, N330, N339, N347, or N375 carbon black), or higher series ASTM grade carbon blacks of the 500, 600, 700, 800, or 900 series (e.g., N550, N660, N683, N772, N774, N880, N990, N991 carbon black).
[0109] According to a more preferred embodiment of the above preferred embodiment, the filler in the rubber powder includes non-reinforcing filler, preferably chalk, kaolin or a combination thereof.
[0110] The rubber powder in the rubber composition according to the invention may consist of a composition based on commonly used additives typically used in rubber compositions intended for use in rubber articles. The additives may also be present in the rubber powder as residues or derivatives, as they are capable of reacting during steps of preparing the composition or during steps of causing the composition to crosslink.
[0111] The rubber powder in the rubber composition according to the present invention can be a simple rubber material that has been ground / micronized without any other treatment.
[0112] The thirteenth aspect of the invention is a rubber composition according to any one of the first to twelfth aspects, wherein the rubber powder has not been modified by any treatment selected from heat treatment, mechanical treatment, biological treatment, chemical treatment, and combinations thereof.
[0113] According to the preferred embodiment of the thirteenth aspect, the rubber powder has more than 3% by weight and less than 30% by weight, preferably more than 3% by weight and less than 15% by weight, and more preferably more than 3% by weight and less than 10% by weight of acetone extract / 100% by weight of rubber powder.
[0114] According to the preferred embodiment of the thirteenth aspect, the rubber powder has more than 3% by weight and less than 85% by weight, preferably more than 3% by weight and less than 20% by weight, and more preferably more than 5% by weight and less than 15% by weight of chloroform extract / 100% by weight of rubber powder.
[0115] According to the preferred embodiment of the thirteenth aspect, the weight-average molecular weight (Mw) of the chloroform extract in the rubber powder is less than 10,000 g / mol, preferably less than 8,000 g / mol.
[0116] According to the preferred embodiment of the thirteenth aspect, the weight ratio of chloroform extract to acetone extract in the rubber powder is less than 1.5.
[0117] According to embodiments of the present invention, the rubber powder in the rubber composition according to the present invention is treated to modify it. This treatment may include chemical functionalization or desulfurization modification. It may also be thermomechanical, thermochemical, biological, or other treatments.
[0118] According to embodiments of the present invention, the rubber powder in the rubber composition of the present invention has a modified form by heat treatment, mechanical treatment, biological treatment, chemical treatment, or a combination thereof. Preferably, the modified rubber powder has more than 5% by weight and less than 20% by weight, more preferably 10% by weight to 18% by weight of acetone extract. Similarly, preferably, the modified rubber powder has more than 15% by weight and less than 85% by weight, more preferably 15% by weight to 50% by weight of chloroform extract. Preferably, the chloroform extract of the modified rubber powder has a weight-average molecular weight (Mw) greater than 10,000 g / mol, more preferably greater than 20,000 g / mol, and even more preferably greater than 30,000 g / mol. Preferably, the weight ratio of chloroform extract to acetone extract in the modified rubber powder is greater than 1.5 or equal to 1.5, preferably greater than 2.
[0119] The amount of acetone or chloroform extract can be measured using a Soxhlet extractor according to standard ISO 1407. The test sample (greater than 500 mg and less than 5 g) can be introduced into the extraction chamber and then placed into the tube of the Soxhlet extractor. Two or three times the volume of acetone or chloroform equal to the volume of the extractor tube can be placed into the Soxhlet collector. The Soxhlet extractor can then be assembled and heated for 16 hours. The sample can be weighed after extraction. The amount of acetone or chloroform extract corresponds to the weight loss of the sample relative to its initial weight during the extraction process.
[0120] Molecular weight can be determined by size exclusion chromatography (SEC) according to molar calibration and standard ISO 16014. The weight-average molecular weight (Mw) of the chloroform extract can be measured by SEC using a refractive index (RI) detector. The system can consist of an Alliance 2695 line from Waters, a column oven from Waters, and an RI 410 detector from Waters. A set of columns can be used consisting of two PL Gel Mixed D columns (300 × 7.5 mm 5 μm) from Agilent, followed by two PL Gel Mixed E columns (300 × 7.5 mm 3 μm). These columns can be placed in a column oven at a constant temperature of 35°C. The mobile phase can be a non-antioxidant tetrahydrofuran. The flow rate of the mobile phase can be 1 ml / min. The RI detector can also be kept at a constant temperature of 35°C. The chloroform extract can be dried under a nitrogen stream. The dried extract can then be dissolved at 1 g / L in 250 ppm of non-antioxidant tetrahydrofuran and stirred for 2 hours. The obtained solution can be filtered using a syringe and a disposable 0.45 μm PTFE syringe filter. 100 μl of the filtered solution can be injected into the calibrated chromatographic system at a rate of 1 ml / min at 35 °C. Mw results can be provided by integrating chromatographic peaks exceeding 2000 g / mol detected by the RI detector. Mw can be calculated using calibration with polystyrene standards.
[0121] The rubber composition according to the invention may be based on all or at least a portion of commonly used additives typically used in rubber compositions intended for use in rubber articles (e.g., tires, shoes, belt conveyors, or rubber tracks), such as fillers other than rubber powder (e.g., reinforcing fillers: reinforcing organic fillers (e.g., carbon black), reinforcing inorganic fillers (e.g., silica) or combinations thereof), coupling agents, plasticizers (e.g., liquid plasticizers (e.g., oils), solid plasticizers (e.g., hydrocarbon resins with or without tackifying resin properties) or combinations thereof), protective agents other than anti-ozone waxes (e.g., chemical anti-ozone agents, antioxidants or combinations thereof), pigments, anti-fatigue agents, reinforcing resins, methylene acceptors (e.g., phenolic varnish resins), methylene donors (e.g., hexamethylenetetramine (HMT), hexamethoxymethylmelamine (H3M) or combinations thereof), processing aids, crosslinking (vulcanization) systems or combinations thereof.
[0122] According to a preferred embodiment of the invention, the rubber composition according to the invention is further based on a crosslinking system.
[0123] According to a more preferred embodiment of the above-described preferred embodiment, the crosslinking system in the rubber composition according to the present invention includes a vulcanizing agent, which is preferably selected from sulfur, sulfur donors, peroxides, bismaleimide, and combinations thereof, and more preferably from sulfur and combinations thereof. The vulcanizing agent is referred to as a "curing agent," "hardening agent," or "aging agent." According to an even more preferred embodiment of the above-described preferred embodiment, the sulfur donor is an alkylphenol disulfide (abbreviated as "APDS"), more preferably a p-(tert-butyl)phenol disulfide. According to an even more preferred embodiment of the above-described preferred embodiment, the total amount of the vulcanizing agent is greater than 0.5 phr and less than 10 phr, preferably greater than 0.5 phr and less than 3 phr.
[0124] According to a more preferred embodiment of the above-described preferred embodiment, the crosslinking system in the rubber composition according to the present invention includes a vulcanization accelerator, wherein the vulcanization accelerator is preferably a primary vulcanization accelerator, more preferably selected from sulfenamide accelerators, thiazole accelerators, thiuram accelerators, dithiocarbamate accelerators, and combinations thereof, and even more preferably selected from sulfenamide accelerators and combinations thereof. According to an even more preferred embodiment of the above-described preferred embodiment, the sulfenamide accelerator is selected from N-cyclohexyl-2-benzothiazole sulfenamide (abbreviated as "CBS"), N-(tert-butyl)-2-benzothiazole sulfenamide (abbreviated as "TBBS"), N-tert-butyl-2-benzothiazole sulfimide (abbreviated as "TBSI"), N-oxodiethyl-2-benzothiazole sulfenamide (abbreviated as "MBS"), N,N-dicyclohexyl-2-benzothiazole sulfenamide (abbreviated as "DCBS"), and combinations thereof. According to a further more preferred embodiment of the above-mentioned preferred embodiment, the thiazole accelerator is selected from 2-mercaptobenzothiazole (abbreviated as "MBT"), 2-mercaptobenzothiazole disulfide (abbreviated as "MBTS"), 2-mercaptobenzothiazole zinc (abbreviated as "ZMBT"), 2-(morpholinothio)benzothiazole (abbreviated as "MDB"), and combinations thereof. According to a further more preferred embodiment of the above-mentioned preferred embodiment, the thiuram accelerator is selected from tetramethylthiuram disulfide (abbreviated as "TMTD"), tetraethylthiuram disulfide (abbreviated as "TETD"), tetrabutylthiuram disulfide (abbreviated as "TBTD"), tetra(2-ethylhexyl)thiuram disulfide (abbreviated as "TOT-N"), tetramethylthiuram monosulfide (abbreviated as "TMTM"), dipentamethylenethiuram tetrasulfide (abbreviated as "DPTT"), tetrabenzylthiuram disulfide (abbreviated as "TBzTD"), and combinations thereof. According to a further more preferred embodiment of the above-mentioned preferred embodiment, the dithiocarbamate accelerator is selected from zinc dimethyl dithiocarbamate (abbreviated as "ZDMC"), zinc diethyl dithiocarbamate (abbreviated as "ZDEC"), zinc dibutyl dithiocarbamate (abbreviated as "ZDBC"), zinc ethylphenyl dithiocarbamate (abbreviated as "ZEPC"), zinc dibenzyl dithiocarbamate (abbreviated as "ZDBzC"), zinc N-pentamethylene dithiocarbamate (abbreviated as "ZPDC"), and combinations thereof. According to a further more preferred embodiment of the above-mentioned preferred embodiment, the total amount of vulcanization accelerator is greater than 0.5 phr and less than 5.0 phr.
[0125] According to a more preferred embodiment of the above-described preferred embodiment, the crosslinking system in the rubber composition according to the present invention includes a vulcanization retarder, such as N-cyclohexylthiophthalimide (abbreviated as "CTP").
[0126] According to a more preferred embodiment of the above-described preferred embodiment, the crosslinking system in the rubber composition according to the present invention includes a vulcanization activator, which is preferably selected from zinc oxide, fatty acids, zinc fatty acid esters, guanidine derivatives, or combinations thereof. According to an even more preferred embodiment of the above-described preferred embodiment, the fatty acid is stearic acid, lauric acid, palmitic acid, oleic acid, naphthenic acid, or combinations thereof. According to an even more preferred embodiment of the above-described preferred embodiment, the zinc fatty acid ester is zinc stearate, zinc laurate, zinc palmitate, zinc oleate, zinc naphthenate, or combinations thereof. According to an even more preferred embodiment of the above-described preferred embodiment, the guanidine derivative is diphenylguanidine.
[0127] The rubber composition according to the invention can be used alone or in the form of a blend (i.e., a mixture) with any other rubber composition that can be used to manufacture rubber articles.
[0128] It goes without saying that the present invention relates to rubber compositions in both the previously described states of an uncured or non-crosslinked or untreated state (i.e., before curing) and a cured or crosslinked or vulcanized state (i.e., after crosslinking or vulcanization).
[0129] According to a preferred embodiment of the invention, the rubber composition according to the invention is further based on a crosslinking system comprising a vulcanizing agent, a vulcanization accelerator, a vulcanization retarder, a vulcanization activator, or a combination thereof. The rubber composition according to the invention is manufactured in a mixer using two consecutive preparation stages: a first stage (referred to as the "non-production" stage) involving thermomechanical operation or kneading at a high temperature up to a maximum of 110°C and less than 200°C, preferably greater than 110°C and less than 190°C, more preferably greater than 130°C and less than 180°C; followed by a second stage (referred to as the "production" stage) involving mechanical operation at a lower temperature less than or equal to 110°C, preferably greater than 40°C and less than 100°C, more preferably greater than 60°C and less than 100°C, during which the vulcanizing agent, vulcanization accelerator, and vulcanization retarder, or a combination thereof, from the crosslinking system are introduced. According to a more preferred embodiment of the above-described preferred embodiment, the vulcanization activator is introduced in the first non-production stage, the production stage, or both, preferably in the first non-production stage.
[0130] According to a more preferred embodiment of the above preferred embodiment, the first stage (non-production stage) is carried out in several thermomechanical steps: during the first step of the several thermomechanical steps, at a temperature greater than 20°C and less than 100°C, preferably greater than 25°C and less than 100°C, the elastomer matrix, rubber powder (and optional anti-ozone wax, other components (other than vulcanizing agents, vulcanization accelerators, vulcanization retarders or combinations thereof in the crosslinking system) or combinations thereof) are introduced into a mixer (preferably a closed mixer); after a few minutes (preferably 0.5 minutes to 2 minutes) and the temperature rises to 90°C or higher (preferably 100°C) After ℃), except for the vulcanizing agent, vulcanization accelerator, vulcanization retarder or combination thereof in the crosslinking system, the elastomer matrix, other components and combinations thereof (i.e. those remaining if not all of them were introduced into the mixer in the first step (non-production stage)) are added at once or in portions during a mixing process ranging from 20 seconds to several minutes; wherein in the first stage (non-production stage), at a temperature of less than or equal to 190°C, preferably less than or equal to 180°C, more preferably less than or equal to 170°C, the total kneading duration is preferably greater than 1 minute and less than 15 minutes, more preferably greater than 2 minutes and less than 10 minutes.
[0131] According to the preferred embodiment described above or an even more preferred embodiment described above, after the mixture obtained therefrom is cooled, the vulcanizing agent, vulcanization accelerator, vulcanization retarder or combination thereof in the crosslinking system is then introduced into an open mixer (preferably an open mill) at a low temperature (preferably less than or equal to 100°C, more preferably less than or equal to 90°C); then in the second stage (production stage), all substances are mixed for several minutes, preferably more than 2 minutes and less than 15 minutes, more preferably more than 5 minutes and less than 15 minutes.
[0132] According to the preferred embodiment, the more preferred embodiment, or the even more preferred embodiment described above, the rubber composition obtained in the mixer through two consecutive preparation stages is then calendered, for example, into the form of sheets or plates for laboratory characterization, or the rubber composition is extruded into the form of rubber molding elements that can be used directly as rubber articles, such as tire sidewalls, tire treads, shoe soles, conveyor belt covers, and rubber track surfaces.
[0133] According to the preferred embodiment, the more preferred embodiment, the even more preferred embodiment, or the more particular embodiment, the crosslinking (or curing) is carried out in a known manner at a temperature greater than 110°C and less than 200°C, preferably greater than 130°C and less than 190°C, and under pressure for a sufficient time, the time range being, for example, between 5 minutes and 90 minutes, the time varying with, in particular, the curing temperature, the crosslinking system used, the crosslinking kinetics of the rubber composition under consideration, or the size of the rubber article.
[0134] According to a preferred embodiment of the invention, the rubber composition is a rubber composition for rubber articles in contact with ambient air, particularly for tires, shoes, conveyor belts or rubber tracks, more particularly for tire sidewalls, tire treads, shoe soles, conveyor belt covers or rubber track surfaces, and even more particularly for tire sidewalls.
[0135] A fourteenth aspect of the present invention is a rubber article comprising a rubber composition according to any one of the first to thirteenth aspects. Preferably, the rubber article comprises a rubber component comprising a rubber composition according to any one of the first to thirteenth aspects. More preferably, the rubber article is a tire, a shoe, a conveyor belt, or a rubber track. Even more preferably, the rubber component is a tire sidewall, a tire tread, a tire rim pad, a shoe sole, a conveyor belt cover, or a rubber track surface. The tire sidewall is one of the tire components designed to contact ambient air but not the ground. The tire tread is one of the tire components designed to contact both ambient air and the ground. The tire rim pad is one of the tire components designed to contact the tire rim and ambient air but not the ground. The conveyor belt is the carrying medium of a belt conveyor system. The conveyor belt cover is one of the conveyor belt components, also called a cover rubber or rubber cover, designed to contact ambient air. The rubber track is a type of continuous track, also called a rubber overlay, rubber track body, or rubber track component, designed to equip tracked vehicles. The rubber track surface is one of the components of a rubber track, designed to come into contact with ambient air and the ground.
[0136] The fifteenth aspect of the invention is a tire comprising a rubber composition according to any one of the first to thirteenth aspects, preferably wherein the tire includes a sidewall comprising a rubber composition according to any one of the first to thirteenth aspects.
[0137] The tires described above in this invention are particularly intended for use in passenger motor vehicles, including 4×4 (four-wheel drive) vehicles and SUVs (sports utility vehicles), as well as in industrial vehicles, particularly those selected from trucks and heavy-duty vehicles (i.e., buses or heavy road transport vehicles (trucks, tractors, trailers)).
[0138] The invention is further illustrated by the following non-limiting embodiments.
[0139] Example
[0140] To demonstrate the effectiveness of the invention, twelve rubber compositions were used (C1 to C5: embodiments according to the invention; T1: reference; T2 to T7: comparative embodiments). Each rubber composition was based on a diene elastomer (a combination of natural rubber (abbreviated "NR") and polybutadiene rubber (abbreviated "BR") as the elastomer matrix), an anti-ozone wax, and with or without rubber powder, said rubber powder comprising rubber powder particles with a particle size of less than 74 μm. Tables 1 and 2 show the formulations of each rubber composition, wherein the amounts of various products are expressed as weight percentage / 100% by weight of each rubber composition. Tables 3 and 4 show each weight ratio of the total amount of rubber powder particles with a particle size of less than 74 μm in each rubber composition to the total amount of anti-ozone wax.
[0141] Each rubber composition is prepared as follows: the elastomer matrix, anti-ozone wax, rubber powder, and various other components, except for sulfur (as a vulcanizing agent) and N-cyclohexyl-2-benzothiazole sulfenamide (abbreviated as "CBS") (as a vulcanization accelerator) in the crosslinking system, are sequentially introduced into a closed mixer having an initial container temperature of approximately 60°C; thus, the mixer is approximately 70% full (volume %). A thermomechanical operation (non-production stage) is then performed in one step, lasting a total of approximately 3 to 4 minutes, until the maximum "drip" temperature of 165°C is reached. The resulting mixture is recovered and cooled, and then the vulcanizing agent and vulcanization accelerator in the crosslinking system are introduced into an open mixer (homogenizer) at 20 to 30°C, where all substances are mixed (production stage) for an appropriate time (e.g., greater than 5 minutes and less than 12 minutes).
[0142] The resulting rubber composition is then calendered into sheets (2 mm to 3 mm thick) or thin sheets of rubber to measure their physical or mechanical properties, or calendered into molding elements that can be used directly as semi-finished tires after cutting, assembling, or cutting and assembling to the required dimensions.
[0143] The ozone resistance of the rubber compositions was measured by the following method: Ten specimens of each rubber composition were prepared by curing at 150°C for 40 minutes in a bell press, cooling at ambient temperature for 1 day, and then placing them in an oven at 77°C in air for 28 days. The ten specimens of each rubber composition were graded at 10% elongation and placed on trapezoidal bodies at different elongation rates ranging from 10% to 100%. The specimen, designated "B15," was obtained from an MFTR (Monsanto) plate with two bead-like structures at the ends for securing the specimen. The "B15" specimen had the following dimensions: 78.5 mm * 15 mm * 1.5 mm. After exposure to 38°C and 50 pphm (parts per hundred million) of ozone for 192 hours, the surface of each specimen was graded according to the number and depth of cracks. This subjective grade ranged from 0 to 5 (0: no cracks; 1 to 4: progressively larger and deeper cracks present; 5: specimen fracture). This means that the lower the subjective rating, the better the ozone performance. Tables 5 and 6 show each difference between the average of all deformation ratings for each sample (C1 to C5 and T2 to T7) and the reference (T1). Negative values in Tables 5 and 6 indicate improved ozone performance relative to the reference (T1).
[0144] The blooming properties of the rubber composition were measured as follows: After cutting from a sheet of the cured rubber composition, 2.5 mm thick samples were heat-treated in air at 70°C for 12 hours. The samples were then heat-treated in air at 40°C for 4 weeks. After removing the samples from the oven and exposing them to ambient temperature for 15 minutes, each sample was scraped with a metal blade to reveal blooming of the anti-ozone wax. The degree of blooming (whitening of the surface) was then assessed using a subjective scale representing the final appearance of the sample. The values of this subjective scale, obtained from the test samples, range from 0 to 3 and correspond to the "blooming grade." These values, ranging from 0 to 3, correspond to the following aspects of the sample:
[0145] 0: No frosting. The scraped surface remains black.
[0146] 1: Slight frost.
[0147] 2: Moderate frost.
[0148] 3: Completely frosted. The scraped surface is white.
[0149] The lower the value, the better the appearance of the blooming performance, i.e., the weaker the blooming. Tables 5 and 6 show each difference between the values of each sample (C1 to C5 and T2 to T7) and the reference (T1). Negative values in Tables 5 and 6 indicate improved blooming performance relative to the reference (T1).
[0150] The results in Tables 4 and 5 show that, compared with the reference (T1), the embodiments (C1 to C5) according to the present invention not only improved the ozone resistance performance but also improved the frosting performance, while the comparative embodiments (T2 to T7) were worse than the reference (T1) in terms of ozone resistance performance, frosting performance, or both.
[0151] In summary, the rubber composition according to the invention can unexpectedly improve blooming properties without compromising ozone resistance.
[0152] [Table 1]
[0153]
[0154] (1) Natural rubber;
[0155] (2) Nd butadiene rubber;
[0156] (3) Anti-ozone wax (from Sasol's "Varazon 4959");
[0157] (4) Rubber powder 1 (rubber powder particles with a particle size less than 74 μm: 12 wt% / 100 wt% of all rubber powder, rubber powder particles with a particle size greater than or equal to 74 μm: 88 wt% / 100 wt% of all rubber powder, particle size measured according to ASTM D5644-01);
[0158] (5) Rubber powder 2 (rubber powder particles with a particle size less than 74 μm: 24 wt% / 100 wt% of all rubber powder, rubber powder particles with a particle size greater than or equal to 74 μm: 76 wt% / 100 wt% of all rubber powder, particle size measured according to ASTM D5644-01);
[0159] (6) Rubber powder 3 (rubber powder particles with a particle size less than 74 μm: 100% by weight / 100% of all rubber powder; rubber powder particles with a particle size greater than or equal to 74 μm: 0% by weight / 100% of all rubber powder, particle size measured according to ASTM D5644-01);
[0160] (7) Rubber powder 4 (rubber powder particles with a particle size less than 74 μm: 0% by weight / 100% of all rubber powder; rubber powder particles with a particle size greater than or equal to 74 μm and less than 180 μm: 100% by weight / 100% of all rubber powder, particle size measured according to ASTM D5644-01); and
[0161] (8) Rubber powder 5 (rubber powder particles with a particle size less than 74 μm: 0% by weight / 100% by weight of all rubber powder; rubber powder particles with a particle size greater than or equal to 74 μm and less than 850 μm: 100% by weight / 100% by weight of all rubber powder, particle size measured according to ASTM D5644-01);
[0162] [Table 2]
[0163]
[0164] [Table 3]
[0165]
[0166]
[0167] [Table 4]
[0168]
[0169] [Table 5]
[0170] Ozone resistance -0.1 -0.6 -0.8 -0.8 -0.4 Frosting performance -2 -2 -2 -1 -2
[0171] [Table 6]
[0172] Ozone resistance 0.0 +0.1 -0.3 -0.2 -0.5 -0.9 +0.4 Frosting performance 0 0 0 0 0 0 -2
Claims
1. A rubber composition, wherein the composition is based on at least: - Elastomer matrix; - Anti-ozone wax; and - Rubber powder; in, The elastomer matrix comprises an isoprene elastomer; The total amount of the isoprene elastomer is greater than 27.00% by weight / 100.00% by weight in the rubber composition; The total amount of the anti-ozone wax is greater than 0.60% by weight / 100.00% by weight of the rubber composition and less than 1.70% by weight / 100.00% by weight of the rubber composition; The rubber powder comprises rubber powder particles with a particle size of less than 74 μm; and The weight ratio of the total amount of rubber powder particles with a particle size of less than 74 μm to the total amount of anti-ozone wax is greater than 0.
65.
2. The rubber composition according to claim 1, wherein, The total amount of the isoprene elastomer is greater than 28.00% by weight / 100.00% by weight in the rubber composition.
3. The rubber composition according to claim 1, wherein, The total amount of the isoprene elastomer is less than 34.00% by weight / 100% by weight in the rubber composition.
4. The rubber composition according to claim 1, wherein, The isoprene elastomer is selected from natural rubber, synthetic polyisoprene, and combinations thereof.
5. The rubber composition according to claim 1, wherein, The elastomer matrix further comprises butadiene elastomer.
6. The rubber composition according to claim 5, wherein, The total amount of butadiene elastomer is less than 31.00% by weight / 100.00% by weight in the rubber composition.
7. The rubber composition according to claim 5, wherein, The total amount of butadiene elastomer is greater than 23.00% by weight / 100.00% by weight in the rubber composition.
8. The rubber composition according to claim 5, wherein, The butadiene elastomer is selected from butadiene polymers, butadiene copolymers, and combinations thereof.
9. The rubber composition according to claim 1, wherein, The total amount of the anti-ozone wax is greater than 0.70% by weight / 100.00% by weight in the rubber composition.
10. The rubber composition according to claim 1, wherein, The total amount of the anti-ozone wax is less than 1.60% by weight / 100.00% by weight of the rubber composition.
11. The rubber composition according to claim 1, wherein, The weight ratio of the total amount of rubber powder particles with a particle size of less than 74 μm to the total amount of anti-ozone wax is greater than 0.
70.
12. The rubber composition according to claim 1, wherein, A rubber composition in which the total amount of rubber powder particles with a particle size of less than 74 μm is greater than 0.90% by weight / 100.00% by weight.
13. The rubber composition according to claim 1, wherein, The rubber powder has not been modified by any treatment selected from heat treatment, mechanical treatment, biological treatment, chemical treatment, and combinations thereof.
14. A rubber article comprising a rubber composition according to any one of claims 1 to 13.
15. A tire comprising a rubber composition according to any one of claims 1 to 13.
Citation Information
Patent Citations
Process and apparatus for manufacturing crumb and powder rubber
US7445170B2
Conical-shaped impact mill
US7861958B2
Tyre having a tread provided with cavities containing a specific filler material
WO2009083160A1
Tyre comprising a rubber composition having a pro-oxidant and a rubber crumb
CN113226786A
Rubber composition and method for producing the same
JP2004238547A